COMMUNICATIVE FUNCTIONS USED BY TED TALK SPEAKERS TO ATTRACT THEIR AUDIENCES - Ryan Marina; Dimas Prasetya (Pusat Riset dan Inovasi Nasional, 2023)
TED stands for Technology, Entertainment, and Design. It is a global set of conferences that has now broadened its focus to include talks on many scientific, cultural, and academic topics (ted.com). This research aimed to identify the kinds of communicative functions used by speakers in TED Talks and which communicative functions are used the most by the speakers to attract their audiences. There were two basic data involved in this study. The first data were TED Talks audio-visual recordings. There were six videos used in this study. The second data was the transcript of the TED Talks. This research adopted the purposive sampling method. The analysis of the functional communicative profile has shown that some communicative functions are used in the same way by TED Talk speakers. Some other functions are more frequently used than others. The most frequently used were the heuristic communicative function and interactional communicative function. This study is expected to enrich the knowledge of teachers and practitioners whose daily lives are close to public speaking and better understand what makes certain public talks and speeches succeeded to captivate their viewers.